Use of creativity in social media marketing communication - Wielgus, Magda (Creativity in Business Practice. Part 2, 2019)
The purpose of the chapter was to show the impact of the use of creativity in marketing communication of brands in social media. It was realized through the analysis of selected examples of campaigns carried out in social media, distinguished by originality, the high interest of recipients and a positive assessment of experts.